Commentary: Leveraging discovery science to advance child and adolescent psychiatric research – a commentary on Zhao and Castellanos 2016. (March 2016) - Mennes, Maarten
Abstract : 'Big Data' and 'Population Imaging' are becoming integral parts of inspiring research aimed at delineating the biological underpinnings of psychiatric disorders. The scientific strategies currently associated with big data and population imaging are typically embedded in so‐called discovery science, thereby pointing to the hypothesis‐generating rather than hypothesis‐testing nature of discovery science. In this issue, Yihong Zhao and F. Xavier Castellanos provide a compelling overview of strategies for discovery science aimed at progressing our understanding of neuropsychiatric disorders. In particular, they focus on efforts in genetic and neuroimaging research, which, together with extended behavioural testing, form the main pillars of psychopathology research. Abstract : Read the full article at doi:10.1111/jcpp.12503